One season in professional cycling is enough to negatively affect bone health - Martínez-Noguera, F. J.; Alcaraz, P. E.; Ortolano-Ríos, R.; Marín-Pagán, C. (Nutrients, 2023)
Cycling is a very popular sport worldwide, and several studies have already indicated that cycling at various levels has a negative impact on bone health. This is of concern to both performance and health managers of many cycling teams at different levels because of its economic and social impact. Based on the scientific literature, we hypothesize that a single season at the professional level can negatively affect bone health status. The aim of this study was to assess how professional cycling affects bone health markers after one season. Densitometry was used to measure the bone mineral density (BMD), bone mineral content (BMC), bone area (BA), fat mass (FM), fat-free mass (FFM), T-score and Z-score in professional cyclists after one season. After one season at the professional level, cyclists` BMD decreased significantly in the legs, trunk, ribs and pelvis (p = 0.05). BMC decreased in the arms and spine (p = 0.05). BA decreased significantly in the arms and spine (p = 0.05). In addition, a significant decrease in Z-score (p = 0.05) and a decreasing trend in T-score and total BMD (p = 0.06) were observed. One season of professional cycling is enough to negatively affect bone health status.